1999
DOI: 10.1073/pnas.96.7.3365
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant bioavailability in soils, sediments, and aquatic environments

Abstract: The aqueous concentrations of heavy metals in soils, sediments, and aquatic environments frequently are controlled by the dissolution and precipitation of discrete mineral phases. Contaminant uptake by organisms as well as contaminant transport in natural systems typically occurs through the solution phase. Thus, the thermodynamic solubility of contaminant-containing minerals in these environments can directly inf luence the chemical reactivity, transport, and ecotoxicity of their constituent ions. In many cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(133 citation statements)
references
References 43 publications
4
127
1
1
Order By: Relevance
“…Instead, PbHPO 4 formation was detected. Although the solubility product of PbHPO 4 (Ksp=10 -23.8 ) is higher than that of pyromorphite-like minerals (Ksp=10 -71.6 -10 -84.4 ), it is still much lower than that of cerussite (Ksp=10 -12.8 ) (Traina & Laperche 1999). Therefore, PbHPO 4 formation would be responsible for the reduction of Pb leachability.…”
Section: Phosphate Treatmentmentioning
confidence: 86%
“…Instead, PbHPO 4 formation was detected. Although the solubility product of PbHPO 4 (Ksp=10 -23.8 ) is higher than that of pyromorphite-like minerals (Ksp=10 -71.6 -10 -84.4 ), it is still much lower than that of cerussite (Ksp=10 -12.8 ) (Traina & Laperche 1999). Therefore, PbHPO 4 formation would be responsible for the reduction of Pb leachability.…”
Section: Phosphate Treatmentmentioning
confidence: 86%
“…Phosphate in soil may affect the chemical reactions of metals on mineral surfaces. Recent studies (Traina and Laperche, 1999;Cao et al, 2002) indicated that phosphate minerals, such as apatite, could sequester heavy metals, metalloids and radionuclide through adsorption and/or the formation of secondary PO 3À 4 precipitates, which remained stable under a wide range of geochemical conditions. Therefore, it is necessary to examine the influence of phosphate on the reactions of heavy metals on the surface of soil minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The potential values of common soil amendments (phosphates, lime, biosolids and coal ash) relative to their ability to immobilize metals such as lead in soil or sediment are discussed by Traina & Laperche (1999), for attenuation of Cd and Zn availability in polluted soil amended with CaCO 3 and KH 2 PO 4 (Hamon et al 2002), for Pb, Cd, As and Hg immobilization with phosphates and lime (Porter et al 2004). For the review of the implications of liming in relation to heavy metal transformation and bioavailability in acidic soils see Bolan et al (2003a) and Adriano et al (2004).…”
Section: Precipitationmentioning
confidence: 99%